INTEGRASI MANAJEMEN KURIKULUM DALAM MENINGKATKAN KUALITAS PEMBELAJARAN: STUDI KUALITATIF DI MI MA’ARIF NU 001 PALARAN - Kurniati, Devi; Yuliani, Eka; Hidayah, Lailatul; Suratman, Suratman; Ramli, Akhmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the integration of curriculum management in improving the quality of learning at MI Ma’arif NU 001 Palaran. As the core instrument of education, the curriculum requires integrated management to effectively address students’ needs and the challenges of the educational environment. This research employs a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving the principal, teachers, and students. The findings reveal that curriculum management integration at MI Ma’arif NU 001 Palaran is carried out through adaptive program planning, contextual implementation of learning activities, and continuous evaluation. Supporting factors include leadership commitment, teacher participation, and parental involvement, while the main obstacles are limited facilities and diverse student abilities. The integration of curriculum management contributes positively to enhancing learning quality across cognitive, affective, and psychomotor domains. This study recommends strengthening teachers’ capacity in curriculum management and improving supporting facilities to ensure sustainable development of learning quality in madrasah education.